APPLICATION OF ORGANIC FERTILIZER AND AEROBIC IRRIGATION SYSTEM ON SEVERAL VARIETIES OF LOWLAND RICE TO INCREASE YIELD OF SOYBEAN DIRECT-SEEDED FOLLOWING RICE - Maemunah Maemunah; Wayan Wangiyana (Jurnal Silva Samalas, 2019)
This study aimed to examine the effect of cultivation techniques of several varieties of lowland rice between conventional techniques and aerobic irrigation systems, and the application of organic fertilization using bokashi (EM-4 fermented) cattle manure, on yield of Anjasmoro variety of soybean direct-dibbled following harvest of rice without tillage, by conducting pot experiment in a plastic house from September to December 2015. The experiment was designed according to factorial Completely Randomized Design consisting of 3 treatment factors, namely rice cultivation techniques (T1: conventional, T2: aerobic irrigation systems), lowland rice varieties (V1: Inpari 23, V2: Inpari 24, V3: Inpari 25), and organic fertilizer (P0: non-organic, P1: with organic fertilizer), and each treatment combination was made in three replications. The seeding of soybean of Anjasmoro variety was done by immediately dibbling the seeds after harvesting rice in accordance with the treatment factors without tillage. The results indicated that rice cultivation techniques and application of organic fertilizer had significant effects on growth and yield components of soybean, and there was an interaction effect but only between cultivation techniques and rice varieties on the trifoliate leaf number at the age of 49 days, but the rice varieties did not affect growth and yield of soybean following rice crops. The seed yield was higher on soybean following rice of aerobic irrigation system (20.65 g/pot) than following conventional rice (17.92 g/pot), and it was higher on pots receiving organic fertilizer (23.29 g/pot) compared to without organic fertilizer (15.28 g/pot). Even without organic fertilizer, seed yield was higher (16.59 g/pot) in soybeans direct-seeded following aerobic rice compared to following conventional rice (13.98 g/pot).